Maternal trans-vaccenic acid shapes neonatal T cell development and early-life immune imprinting - Hao Fan; Zhong Zheng; Kaitlyn Oliphant; Jiacheng Li; Ryan Mack; Cheng-Wei Ju; Brandon Trandai; Jiayi Tu; Freya Q. Zhang; Rukang Zhang; Zhicheng Xie; Chunzhao Yin; et al. (Science, 2026)
How maternal nutrition influences neonatal immune development and imprinting through breastfeeding remains largely unclear. We report that maternal supplementation with trans-vaccenic acid (TVA), the predominant naturally occurring trans-fatty acid in human breast milk, promoted neonatal T cell development in mice. Neonates fed by mothers on a TVA-enriched diet showed an expanded naïve cluster of differentiation 4 (CD4 + ) T cell population and enhanced adaptive immunity against infection. TVA reprogrammed neonatal naïve CD4 + T cells through a G protein–coupled receptor–CCCTC-binding factor axis and promoted T helper cells (Th1)–skewing by cooperating with the transcription factor TBX21. Early-life exposure to maternal TVA via breastfeeding supported long-lasting antiviral immunity in adulthood. Our findings establish the multifaceted benefits of maternal nutrition and breastfeeding via TVA in promoting infant immune homeostasis and protective immunity.